2020
DOI: 10.3390/su12176752
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Relations among Motivation, Self-Perceived Use of Strategies and Academic Achievement in Science: A Study with Spanish Secondary School Students

Abstract: The relationship between motivation and the use of learning strategies is a focus of research in order to improve students’ learning. Meaningful learning requires a learner’s personal commitment to put forth the required effort needed to acquire new knowledge. This commitment involves emotional as well as cognitive and metacognitive factors, and requires the ability to manage different resources at hand, in order to achieve the proposed learning goals. The main objectives in the present study were to analyse: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Such a state produces in the student an inability to adapt to the demands that are present in the university academic environment [17,18]. Academic stress is not only found in the university environment however, but is specific to each of the academic stages (e.g., secondary, primary and infant), although it is during the university stage that the stress reaches its highest point due to the high demands of this stage [2,19].…”
Section: Academic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a state produces in the student an inability to adapt to the demands that are present in the university academic environment [17,18]. Academic stress is not only found in the university environment however, but is specific to each of the academic stages (e.g., secondary, primary and infant), although it is during the university stage that the stress reaches its highest point due to the high demands of this stage [2,19].…”
Section: Academic Stressmentioning
confidence: 99%
“…Studies focusing on metacognitive strategies in education have shown a positive relationship with respect to academic performance [19,30], achievement of learning objectives [31], reading comprehension [32] and second-language learning [33].…”
Section: Metacognitive Strategies and Critical Thinkingmentioning
confidence: 99%
“…The questionnaire is valid for the complete sample, as it has been used before with the same ages: for secondary students Ortega-Torres et al [25] and university students Ramirez-Echeverry et al [26].…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Wipawayangkool et al ( 48 ) argue that self-efficacy provides a buffer mechanism for students to deal with stressors, and the inability to handle stress rationally is an important reason for the phenomenon of burnout. Self-efficacy negatively predicts the phenomenon of burnout ( 49 ). Students’ low self-efficacy due to failure to meet expectations or lack of coping strategies can cause them to become apathetic to learning and eventually deplete their energy.…”
Section: Introductionmentioning
confidence: 99%